Are We Reading or Playing? Functions of Ludic Discourse in Electronic Picture Books (Preučevanje otroške in mladinske književnosti, 2025)
The electronic picture book is a multimodal work characterised by features from the new media environment, such as interactivity, hypertextuality, simulation, and virtuality. In such works, interactivity can be manifested as a feature of a new media work but also as an essential element in constructing the picture book narrative, that is, as a specific discourse. Unlike verbal, visual, and auditory discourse, ludic discourse is not made up of media objects but is based on the reader's interaction with the literary work, which influences the discursive characteristics of other media objects. Using the example of The Big Word Factory electronic picture book for iOS and Android devices (Mixtvision 2018), based on a printed picture book by Agnès de Lestrade and illustrated by Valerie Docampo, the paper will explore the relationship between the features of digital media and the function of ludic discourse within the picture book narrative.